Education policy implementation A literature review and proposed framework - Viennet, Romane (OECD Education Working Papers, 2017)
This literature review focuses on education policy implementation, its definition, processes and determinants. It aims to clarify what implementing policies involve in complex education systems to support policy work, building on the literature and country examples. An introduction delves into the reasons behind the need to update the concept of education policy implementation, which is defined as a purposeful and multidirectional change process aiming to put a specific policy into practice and which affects an education system on several levels. The paper then analyses the determinants that hinder or facilitate the process and groups them under four dimensions which support effective implementation: smart policy design, inclusive stakeholder engagement, conducive context and a coherent implementation strategy. Based on these dimensions, the paper proposes a generic framework and a complementary set of questions and principles for action that can guide policy makers to design, analyse and carry out their education policy implementation processes